High rejection, low selection: How 'punitive parties' shape ethnic minority representation. (March 2022) - English, Patrick
Evidence suggests that as public opinion towards immigration becomes more negative, so the descriptive representation of ethnic minority groups is increasingly restricted. Recently, some initial research into the causal mechanism hinted that this effect is driven by patterns of candidacy. This suggests that political parties are creating an 'ethnic penalty' of their own in the selection stage. This paper investigates the relationship between patterns of candidacy, party strategy, and public opinion in Great Britain from 1997 to 2019, and proposes that 'punitive parties' are strongly responsible for shaping the representational outcomes of minority groups. I find support for earlier suggestions that parties are increasingly likely to place ethnic minority candidates away from 'winnable' contests as anti-immigrant hostility rises. These findings are important for our conceptions of ethnic penalties, of party behaviour in selection processes, and for the study and cause of improving political representation.